Tension Pneumothorax During Surgery for Thoracic Spine Stabilization in Prone Position - Demicha Rankin MD; Paul S. Mathew MD; Lakshmi N. Kurnutala MD; Suren Soghomonyan MD, PhD; Sergio D. Bergese MD (SAGE Publishing, 2014)
The intraoperative progression of a simple or occult pneumothorax into a tension pneumothorax can be a devastating clinical scenario. Routine use of prophylactic thoracostomy prior to anesthesia and initiation of controlled ventilation in patients with simple or occult pneumothorax remains controversial. We report the case of a 75-year-old trauma patient with an insignificant pneumothorax on the right who developed an intraoperative tension pneumothorax on the left side while undergoing thoracic spine stabilization surgery in the prone position. Management of an intraoperative tension pneumothorax requires prompt recognition and treatment; however, the prone position presents an additional challenge of readily accessing the standard anatomic sites for pleural puncture and air drainage.